2019
DOI: 10.1055/s-0039-1677722
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Patients during Hospitalization: Perspectives on Inpatient Portal Use

Abstract: Background Patients have demonstrated an eagerness to use portals to access their health information and connect with care providers. While outpatient portals have been extensively studied, there is a recognized need for research that examines inpatient portals. Objective We conducted this study to improve our understanding about the role of a portal in the context of inpatient care. Our study focused on a large sample of the general adult inpatient population and obtained perspectives from both pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 34 publications
4
29
0
Order By: Relevance
“…A qualitative, retrospective study (McAlearney, 2019), found early indications that inpatient portals "promoted independence, reduced anxiety, informed families, and increased patient empowerment, overall." A randomized trial (Masterson, 2019) concluded that inpatient portals resulted in a decreased 30-day readmission rate.…”
Section: Commentarymentioning
confidence: 99%
“…A qualitative, retrospective study (McAlearney, 2019), found early indications that inpatient portals "promoted independence, reduced anxiety, informed families, and increased patient empowerment, overall." A randomized trial (Masterson, 2019) concluded that inpatient portals resulted in a decreased 30-day readmission rate.…”
Section: Commentarymentioning
confidence: 99%
“…9,12,[15][16][17][18] In recent years, health care systems have been trying to engage patients by offering online access to their health records via patient portals, and reported experiences regarding implementation of patient portals for acute care are now starting to emerge. 15,[19][20][21][22][23][24][25][26][27] Still, few studies have demonstrated meaningful impact on key outcomes, 20,[28][29][30] and to our knowledge, none have demonstrated the potential for using patient portals to improve concordance about the care plan, including recovery goals, among patients and clinicians in the acute care setting. 23,31,32 Improving patient-clinician communication through the meaningful use of patient portals represents a promising strategy to enhance mutual understanding about the plan and facilitate goal-concordant care for seriously ill patients during hospitalization and the transition back to the ambulatory setting.…”
Section: Background and Significancementioning
confidence: 99%
“…14 Patients and caregivers participants have generally shown willingness to use these portals and found them useful. 9,[15][16][17][18][19] Less is known about clinician expectations of inpatient portals and the effects of use on their work, particularly among inpatient nurses and support staff. 20 Pell et al 21 evaluated hospitalized patients' (50) and clinicians' (28 physicians; 14 nurses) experiences using an inpatient portal before and after implementation on a single medical unit.…”
Section: Background and Significancementioning
confidence: 99%